Field reports, Spring 1993, Jim Dinsmore - Dinsmore, James J.et al (1993)
An annotated list of birds sighted by Jim Dinsmore and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1993. Plustek - flatbed